Cationic AuIII versus AuI: Catalyst‐Controlled Divergent Reactivity of Alkyne‐Tethered Lactams. Issue 13 (6th February 2017) - Alcaide, Benito; Almendros, Pedro; Cembellín, Sara; Fernández, Israel; Martínez del Campo, Teresa
Abstract: Switchable reactivity through cationic gold‐based catalyst control built on the oxidation state, namely cationic Au III versus Au I, has been achieved in the direct functionalization of 2‐azetidinone‐tethered alkynyl indoles. Abstract : Going golden : Switchable reactivity through a cationic gold‐based catalyst control built on the oxidation state, namely cationic Au III versus Au I, has been achieved in the direct functionalization of 2‐azetidinone‐tethered alkynyl indoles.